241. Reducing Fluoroquinolone Use Through Implementation of a Urinary Tract Infection (UTI) Treatment Pathway and Healthcare Provider Education: A Pre- and Postintervention Study. (26th November 2018) - Little, Erica; Land, Nikki; Peters, Brian; Ikerd, Tracey
Abstract: Background: Fluoroquinolones are associated with significant adverse effects, including tendinitis, Clostridium difficile infection, and central nervous system side effects, especially when used in older adults. Additionally, there is a trend of increasing resistance of Escherichia coli and other Gram-negative organisms to fluoroquinolones. The objective of this study was to decrease the inappropriate use of fluoroquinolones for treatment of urinary tract infections in patients either admitted to or seen in the outpatient setting of this institution through implementation of a UTI treatment pathway and targeted provider education. Methods: A retrospective chart review was conducted. A query of the electronic medical record was used to identify patients with a diagnosis of UTI who were prescribed a fluoroquinolone. Data collected included baseline demographics, antibiotic allergies, culture data, days of therapy, and reported adverse events. A letter to healthcare providers focusing on fluoroquinolone avoidance in UTI treatment was distributed, and a new UTI treatment pathway was published in a newsletter sent to healthcare providers and posted throughout the institution. The primary endpoint of the study was the appropriateness of fluoroquinolone use for treatment of UTI before and after the intervention. Secondary endpoints included duration of therapy and percentage of patients prescribed a fluoroquinolone for UTI vs. other antibiotics. Results: A total of 212 patient charts were reviewed, 159 patients in the preintervention group and 53 in the postintervention group. In the preintervention group, use was appropriate in 19% (30/159) of patients who received a fluoroquinolone vs. 47.2% (25/53) in the postintervention group ( P < 0.001). In the inpatient setting, appropriateness of use increased from 24.1% in the preintervention group to 57.1% in the postintervention group ( P = 0.007). In the outpatient setting, appropriateness of use increased from 16% to 40.6% ( P = 0.005). Conclusion: Implementation of a clinical pathway, along with provider education, demonstrated a statistically significant reduction in the inappropriate use of fluoroquinolones for the treatment of UTI in both the inpatient and outpatient setting. Disclosures: All authors: No reported disclosures.